EFFECTIVENESS OF POST-EMERGENCE HERBICIDES APPLICATION ON AREAS OF CORN GROWN FOR GRAIN - Milenko О. H.; Solod, I. S.; Mohylat, P. H.; Hryn, M. E.; Veherenko, V. S. (Scientific Progress & Innovations, 2020)
In order to satisfy the national needs and increase the export of corn grain, modern crop growing faces the task of significantly increasing this crop yield. The fact that weeds negatively affect crop yields and ob-tained product quality, favor spreading pests and diseases, and ultimately increase crop growing products’ cost, does not require any proofs. Therefore, the issues of studying and implementing effective measures to reduce weed infestation level of corn grain areas are relevant. The aim of our research was to establish the effectiveness of post-emergence herbicides in the areas of corn grown for grain. To do this, an experiment in the production conditions was established in five variants: Control (without herbicides and manual weeding); spraying with Pik, 20 g/ha, Milagro, 0.2 l/ha, Eliumis, 2 l/ha, Prima Forte, 0.5 l/ha during the period of 2018–2020. Crops were sprayed with herbicides in the phase of 3 leaves in corn plants. The re-search program was aimed at solving the following tasks: to specify weed species composition, to determine the effect of herbicides on the number of weeds, calculate the density of corn plants depending on the exper-iment variants, determine the impact of weed control measures on corn yield and to establish the economic effectiveness of post-emergence herbicides application on corn areas. Experimental studies have shown that only some herbicides are effective against monocotyledonous and dicotyledonous weeds. Corn yield losses because of weeds can be over 50 %. Among the studied preparations, only Milagro and Eliumis were effec-tive against the grass weeds. Grass weeds proved to be resistant to Pik and Prima Forte preparations. The mortality of dicotyledonous weeds was the highest after applying Prima Forte preparation. Eliumis prepara-tion provided the best biological and economic effectiveness in the system of protection of corn areas from weeds. Thus, for production conditions, it is recommended to use chemical method of weed control applying Eliumis preparation in the amount of 2 l/ha in the technology of growing corn for grain under mixed type of field weed infestation.